Hemangioma with growth inhibition by intermittent compression. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
Case report. A 40-day-old little girl was observed due to the presence of three hemangiomas localized to the left deltoid region, the right leg and the right retroauricular region. The biggest hemangioma of the deltoid region had become evident as a flat, pink patch in the second week of life. The physical examination reserved a curiosity: a straight line deeper than the hemangioma proliferation with greyish background sharply divided the hemangioma in two portions to remember a coffee bean (Fig. 1). When placing the baby on the examining table, we noted that the gray line corresponded perfectly to the fold that formed during the Moro reflex. This is why we assumed as possible responsible factor the intermittent spontaneous compression practicing on hemangioma in that position. After two months hemangioma expanded and grew but the straight line was much less evident (Fig. 2).